Species and Microhabitat of Crabs in Lantangpeo Mangrove Tanakeke Islands South Sulawesi - Dody Priosambodo; A Evi Erviani (Universitas Hasanuddin, 2018)
Research about crabs species (brachyura) in Lantangpeo, Tanakeke Islands, South Sulawesi has been conducted. The aim of this research was to know the crabs species on different type of mangrove microhabitat. Crabs collected with purposive sampling method in mangrove forest around the coastline, tidal creek, fish pond and sheltered waters between Lantangpeo island and Tanakeke island. From sampling activities there were found 28 species of crabs from 13 families. The number of crabs species in mangrove forest around the coastline were higher compared to another type of microhabitat. On the contrary, converted mangrove area (fish pond) were only supported least crabs species. It can be concluded that microhabitat in mangrove forest around the coastline supported more crabs species.